The Impact of Cashless Payment Adoption on Sales Growth in Retail Microenterprises - Aldo Prasetya; Nabila Rahmawati; Kevin Mahardika (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The rapid development of digital financial technology has accelerated the adoption of cashless payment systems among microenterprises, particularly in the retail sector. Digital payment platforms such as Quick Response Code Indonesian Standard (QRIS), electronic wallets, mobile banking, and debit or credit cards have transformed the way businesses conduct transactions by improving payment efficiency, reducing cash handling, and enhancing customer convenience. Despite the increasing implementation of cashless payment systems, empirical evidence regarding their impact on sales growth among retail microenterprises in Indonesia remains limited. This study aims to examine the effect of cashless payment adoption on sales growth in retail microenterprises. A quantitative explanatory research design was employed using a survey of 172 owners and managers of retail microenterprises operating in several regions of Indonesia. Cashless payment adoption was measured through transaction convenience, payment speed, security, accessibility, and customer acceptance, while sales growth was assessed using indicators of revenue growth, transaction frequency, customer acquisition, repeat purchases, and business expansion. The findings indicate that cashless payment adoption has a positive and statistically significant effect on sales growth. Retail microenterprises that actively implement digital payment systems experience higher transaction volumes, improved customer satisfaction, and stronger sales performance compared with businesses relying primarily on cash transactions. The study highlights the strategic role of digital payment adoption in strengthening business competitiveness and accelerating digital transformation among microenterprises. The findings provide practical implications for business owners, financial institutions, and policymakers in promoting broader adoption of cashless payment systems to support sustainable growth in Indonesia's retail microenterprise sector.